Self-referencing rates in biological disciplines - Cascarina, Sean M. (Frontiers in Research Metrics and Analytics, 2023)
The use of citation counts (among other bibliometrics) as a facet of academic research evaluation can influence citation behavior in scientific publications. One possible unintended consequence of this bibliometric is excessive self-referencing, where an author favors referencing their own publications over related publications from different research groups. Peer reviewers are often prompted by journals to determine whether references listed in the manuscript under review are unbiased, but there is no consensus on what is considered "excessive" self-referencing. Here, self-referencing rates are examined across multiple journals in the fields of biology, genetics, computational biology, medicine, pathology, and cell biology. Median self-referencing rates are between 8-13% across a range of journals within these disciplines. However, self-referencing rates vary as a function of total number of references, number of authors, author status/rank, author position, and total number of publications for each author. Importantly, these relationships exhibit interdisciplinary and journal-dependent differences that are not captured by examining broader fields in aggregate (e.g., Biology, Chemistry, Physics, etc.). These results provide useful statistical guidelines for authors, editors, reviewers, and journals when considering referencing practices for individual publications, and highlight the effects of additional factors influencing self-referencing rates.